การพัฒนาระบบการให้คำปรึกษานิสิตนักศึกษาสำหรับสถาบันอุดมศึกษาในกรุงเทพมหานคร - ชรีย์นาท จิตต์บรรเทา (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The aim of this research was to analytically study and synthesize the concept of the development of a student advising system for higher educational institutions in Bangkok. The study procedures comprised of current developments in student advising systems, the development of student advising systems and evaluating the student advising system for higher educational institutions in Bangkok. Institutions selected for study were based on the category of higher institutions and the majors offered according to the International Standard Classification of Education (ISCED, UNESCO, 1997). There were three sampling groups (1) 20 Academic administrators and Student Affairs administrators (2) 166 freshmen advisors (3) 330 freshmen students. The research tools were content analysis, interviews, surveys, opinion questionnaires, advising activity development forms, and assessments. Method of data analysis was content analysis, descriptive statistics, means, percentage, standard deviation and t-tests. Results of study were as following: 1. The process of student advising system for higher educational institutions in Bangkok comprised of input, processes, output and feedback. 2. Total means of the development of a student advising system for higher educational institutions in Bangkok showed that there was a moderate level for administrators (X̅ = 3.38), high level for advisors (X̅ = 3.72) and students (X̅ = 3.70) respectively. Problems and challenges identified in advising administration were insufficient budget allocations for developing advising systems. 3. The development of a student advising system for higher educational institutions in Bangkok consisted of (1) Rationales (2) Objectives (3) Responsible Units (4) Implementations (5) Evaluation Activities such as conducting 11 briefing activities for 90-120 minutes per time. 4. Evaluation of the student advising system for higher educational institutions in Bangkok revealed that there was a significant difference between before and after the research study at 0.05. Students were developed in terms of virtues, ethics, knowledge, individual relations and responsibilities, and the percentage of satisfaction level towards the development of student advising system was highly important at 88.89